Spider Bites: Symptoms & Treatment Options - Barnum, DO, April L. (Osteopathic Family Physician, 2018)
There are around 100,000 species of spiders worldwide. Spiders can be found in garages, basements, attics, cabinets, sheds, gardens, woodpiles, in garbage, under tree bark, and inside of homes. Spiders have four pairs of legs and fangs at the ends of their mouths to bite prey and inject venom. Spider bites are relatively rare. However, spiders may bite when they feel threatened, such as when they are wedged between a part of the human body and an object. Most spider bites are harmless, as spider venom is not thought to be toxic to humans. Generally, a spider will not bite multiple members of the same household. Some spider bites are painful, while other bites are painless. A spider bite will usually resolve on its own within 7-10 days. The skin site should be watched, as spider bites can get infected.